السياسة الخارجية الجزائرية و التحولات الأمنية في منطقة الساحل الإفريقي - جدو, فؤاد (revue mofakir, 2018)
The African coast witnesse ddifferent social, political and economic changes especially after the events of September 11th 2001 where the causal movements became varied frome thnical problems between AZWED movement and the financial government to the spread of terroristic movements. That resulted in a menace for the existence of Mali affectingit and makingit an open area to the external interventions. Due to itsgeo political proximity (neighbouring) to Algeria, these political and security changes influenced all neigh bouring countries including Algeria especially after the collapse of the previous Libyan system. The latter led to the adoption of an approachat the level of foreignpolicy to find political remedy and creating opportunities for dialogue between factions (groups) in Mali and Libya as a political approach to treat a complicated issue though the adoption of dialogue and others’ acceptance far from the military launch which was a failure.